FORMATION OF THE SUBJECTIVITY OF A PRESCHOOL CHILD DURING PHYSICAL AND SPORTS ACTIVITY - Sosunovsky V.S.; Zagrevskaya A.I.; Shelgacheva A.M.; Akaneeva E.A. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to consider the content of the process of formation of the subjectivity of a preschooler during physical culture and sports activities. Results and conclusions. The article presents a theoretical and methodological substantiation of the use of a personality-centered approach in the process of physical education of preschoolers, which focuses on the process of forming the subjectivity of preschool children. The content of the pedagogical aspect of the developed system of physical education of preschool children in the conditions of modern modernization of preschool education is considered.